2003
DOI: 10.1292/jvms.65.145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electroacupuncture on Minimum Alveolar Concentration of Isoflurane in Dogs.

Abstract: ABSTRACT. The effect of electroacupuncture (EA) on minimum alveolar concentration (MAC) of isoflurane was evaluated in dogs. After determination of baseline MAC, EA was applied at each acupoints (LI-4, SP-6, ST-36 and TH-8) and nonacupoint for 30 min. MAC was determined again. EA at acupoints significantly lowered the MAC of isoflurane in dogs (17.5 ± 3.1%, 21.3 ± 8.0%, 21.2 ± 7.5% and 15.4 ± 3.1%, respectively). In control group and nonacupoint electrical stimulation group MAC were not decreased significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Study results demonstrated the alternating frequency of 2 Hz with 100 Hz provided significantly best analgesia, shortened time to extubation and lowest anesthetic use. [22][23][24][25][26][27] Another study evaluated 80 human surgery patients undergoing craniotomy for supratentorial tumor resection. The study investigated the supplementary effect of EAP combined with 2% sevoflurane and its influence on sevoflurane concentration and speed of recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study results demonstrated the alternating frequency of 2 Hz with 100 Hz provided significantly best analgesia, shortened time to extubation and lowest anesthetic use. [22][23][24][25][26][27] Another study evaluated 80 human surgery patients undergoing craniotomy for supratentorial tumor resection. The study investigated the supplementary effect of EAP combined with 2% sevoflurane and its influence on sevoflurane concentration and speed of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected, as based on results from other investigations, the additional analgesia provided by perioperative use of dry needle or electro-acupuncture can significantly decrease anesthetic use. 13,14,[22][23][24][25][26][27][28] It has been demonstrated that morphine, by providing supplemental analgesia during surgery, can lower inhalant anesthetic use by as much 60%. 8 Jeong demonstrated with EAP settings similar to the present study, significant lowering of minimal alveolar concentration of isoflurane in anesthetized dogs with EAP administered at 20Hz frequency for 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of hemodynamic parameters followed the procedure of Jeong [8]. Cardiac index (CI) was expressed as the cardiac output divided by the dog's body weight at the time of the control study.…”
Section: Methodsmentioning
confidence: 99%
“…Um dos princípios envolve escolher pontos proximais e distais à área afetada. Contudo, protocolos já estudados podem ser úteis para a melhor escolha dos acupontos (KLIDE & GAYNOR, 2006). BINAO (IG 14) localiza-se na tuberosidade deltóidea, onde se insere a parte acromial do músculo deltóide, a uma profundidade de 1cm (Figura 1).…”
Section: Principais Pontos Analgésicosunclassified